Application of Waterfall SDLC Method in Designing Student's Web Blog Information System at the National University: Application of Waterfall SDLC Method in Designing Student's Web Blog Information System at the National University - Evans Bayu Kristanto; Septi Andrayana; Benramhman Benramhman (Jurnal Mantik, 2020)
Web Blog as a means of writing for several people, including writers. The design of this web blog information system aims for students to make work in the form of articles about knowledge, personal experience, tutorials, or troubleshooting, news and others, about any writing that is not violates the rules of writing or can hurt the relationship / offend others. Web applications / services make it easier for users to publish an information they have through writing that is made into a post on a web. The blog also consists of various texts, images, hypertext, and several links (which connect several pages - pages from other web sites, audio, video, and other files). Students can interact and share all the information in the National University room with the aim to help students get the information sought. The software development method is done by using the SDLC Waterfall method. This website that is used dynamically presents information that is always up to date. From the results of research that has been carried out the author implements the results of these studies on: Design of the National University Web Blog Blog Information System Using the Waterfall Method.